Thematising intercultural collaboration: Discursive constructions of challenges and opportunities. (December 2013) - Holmgreen, Lise-Lotte; Askehave, Inger
Taking a critical discursive approach (Potter and Wetherell, 1987; Wetherell and Potter, 1988, 1992) to analysing interview data, the article discusses the possible implications of top and middle managers' constructions of intercultural collaboration for the day-to-day workings of a Danish–Ukrainian software company. Of particular interest is the extent to which divergent and contesting understandings may lead to positive synergies or conflict, and whether managers' reflections may function as a means of justifying a particular mindset or course of action, provoking either contestation or acceptance within the organisation (e.g. Parker, 2000). Thus, the findings provide insight into the relation between discourse, that is, talk as (inter)action, and the development and enactment of organisational culture, contributing valuable and practice-oriented knowledge to the field of cross-cultural management. The data for the analysis are derived from 10 semi-structured interviews, which were conducted in the Danish headquarters and the Ukrainian division, respectively, securing a broad intraorganisational representation of voices.